Unveiling the Potential of ICT as a Growth Driver in Egypt - Said, Rama; Ragab, Adla; Sakr, Hala; Esam, Mona (International Journal of Economics and Financial Issues, 2026)
This study examines the role of information and communications technology (ICT) in driving economic growth, with a focus on Egypt. Using the autoregressive distributed lag (ARDL) cointegration approach of Pesaran et al. (2001), Kaldor’s first and third growth laws were estimated for the period 1983–2021. The absence of a comprehensive and consistent employment dataset precluded the estimation of the second law. To address a similar data gap in the third law, we proposed an alternative specification, using total factor productivity (TFP) to capture the overall effect of the ICT sector on the economy. The findings show that the ICT sector proxied by telecommunications, has potential to stimulate economic growth. However, its contribution is largely through adding value to the economy as a producing sector, while its ability to enhance productivity in other sectors remains underutilized. Barriers such as digital divide, low ICT adoption by SMEs, and institutional constraints hinder broader impacts. This study contributes to the literature by proposing a new formulation for Kaldor’s third law, applying Kaldor’s growth framework to assess ICT as a growth driver, and offering the first empirical evaluation of ICT’s role in Egypt’s economic growth using Kaldor’s laws.